Enzymatic activities produced by mixed Saccharomyces and non-Saccharomyces cultures : relationship with wine volatile composition - Maturano, Yolanda Paola; Assof, Mariela Vanesa; Fabani, Maria Paula; Nally, María Cristina; Jofre, Viviana Patricia; Rodriguez Assaf, Leticia Anahi; Toro, Maria Eugenia; Vazquez, Fabio; Castellanos de Figueroa, Lucía Inés (2017)
During certain wine fermentation processes, yeasts, and mainly non-Saccharomyces strains, produce and secrete enzymes such as b-glucosidases, proteases, pectinases, xylanases and amylases. The effects of enzyme activity on the aromatic quality of wines during grape juice fermentation, using different co-inoculation strategies of non-Saccharomyces and Saccharomyces cerevisiae yeasts, were assessed in the current study. Three strains with appropriate enological performance and high enzymatic activities, BSc562 (S. cerevisiae), BDv566 (Debaryomyces vanrijiae) and BCs403 (Candida sake), were assayed in pure and mixed Saccharomyces/non-Saccharomyces cultures. b-Glucosidase, pectinase, protease, xylanase and amylase activities were quantified during fermentations. The aromatic profile of pure and mixed cultures was determined at the end of each fermentation. In mixed cultures, non-Saccharomyces species were detected until day 4–5 of the fermentation process, and highest populations were observed in MSD2 (10 % S. cerevisiae/90 % D. vanrijiae) and MSC1 (1 % S. cerevisiae/99 % C. sake). According to correlation and multivariate analysis, MSD2 presented the highest concentrations of terpenes and higher alcohols which were associated with pectinase, amylase and xylanase activities. On the other hand, MSC1 high levels of b-glucosidase, proteolytic and xylanolytic activities were correlated to esters and fatty acids. Our study contributes to a better understanding of the effect of enzymatic activities by yeasts on compound transformations that occur during wine fermentation.